Raffinose family oligosaccharides (RFOs): role in seed vigor and longevity. Issue 10 (28th October 2022) - Salvi, Prafull; Varshney, Vishal; Majee, Manoj
Abstract: Seed vigor and longevity are important agronomic attributes, as they are essentially associated with crop yield and thus the global economy. Seed longevity is a measure of seed viability and the most essential property in gene bank management since it affects regeneration of seed recycling. Reduced seed life or storability is a serious issue in seed storage since germplasm conservation and agricultural enhancement initiatives rely on it. The irreversible and ongoing process of seed deterioration comprises a complex gene regulatory network and altered metabolism that results in membrane damage, DNA integrity loss, mitochondrial dysregulation, protein damage, and disrupted antioxidative machinery. Carbohydrates and/or sugars, primarily raffinose family oligosaccharides (RFOs), have emerged as feasible components for boosting or increasing seed vigor and longevity in recent years. RFOs are known to perform diverse functions in plants, including abiotic and biotic stress tolerance, besides being involved in regulating seed germination, desiccation tolerance, vigor, and longevity. We emphasized and analyzed the potential impact of RFOs on seed vigor and longevity in this review. Here, we comprehensively reviewed the molecular mechanisms involved in seed longevity, RFO metabolism, and how RFO content is critical and linked with seed vigor and longevity. Further molecular basis, biotechnological approaches, and CRISPR/Cas applications have been discussed briefly for the improvement of seed attributes and ultimately crop production. Likewise, we suggest advancements, challenges, and future possibilities in this area.